Ceramic reinforced magnesium alloy based on composite magnetic field treatment and die casting process thereof
By adding rare earth magnesium intermediate alloy and nano-scale ceramic particles to the magnesium alloy melt, and using electromagnetic stirring technology with composite magnetic field treatment, the problem of poor tissue uniformity during casting of magnesium alloy is solved, significantly improving its hardness and tensile strength , broadened its application areas.
Patent Information
- Application Number
- CN202510031965.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the casting process, magnesium alloy materials have limited their large-area application due to their poor uniformity of the original casting structure, large structure and poor mechanical properties.
Using ceramic reinforced magnesium alloy process based on composite magnetic field treatment, the microstructure and structure of the alloy are improved by adding rare earth magnesium intermediate alloys and nano-scale ceramic particles to the magnesium alloy melt, and using composite electromagnetic stirring technology of rotating magnetic field and pulsed magnetic field. Uniformity.
It significantly improves the hardness, tensile strength and elongation of magnesium alloy, improves its mechanical properties and tissue uniformity, thereby broadening its application areas.
Smart Images

Figure CN119433274A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a ceramic reinforced magnesium alloy based on composite magnetic field treatment and a die-casting process thereof, belonging to the technical field of metal materials. Background Art
[0002] Magnesium alloy materials are characterized by low density, one-third lighter than aluminum, and higher strength than aluminum alloys. They are lightweight, anti-electromagnetic interference, good shielding performance, high strength, sound absorption, good thermal conductivity, and corrosion resistance. They are widely used in automobiles, 3C, aerospace, and national defense. However, due to the poor uniformity of the original casting structure, coarse structure, and poor mechanical properties, the large-scale application of magnesium alloys is limited. The casting process is the basis for obtaining ingots with stable chemical composition and uniform structure. Whether the casting method and process are appropriate is directly related to the quality of the ingot.
[0003] Magnesium alloy cold chamber die casting is to pour a certain amount of molten magnesium into the die-casting machine barrel, then hydraulically inject the molten magnesium into the mold cavity, and form a die-cast product after cooling.
[0004] The pulse and rotating magnetic field generator includes a copper coil, a pulse power supply and a circuit pipeline. The pulse magnetic field treatment is to wrap the copper coil around a circular space of a certain size and apply a pulsed electromagnetic field. The rotating magnetic field generator includes a skeleton, a salient pole silicon steel yoke and a copper coil. Six salient pole silicon steel yokes of equal size are evenly distributed on the skeleton. On each yoke, six coil windings of the same specification are wound by a copper coil to apply a rotating electromagnetic field.
[0005] With the rapid development of metal matrix composite material preparation technology, ceramic particle reinforced magnesium alloy corrosion-resistant and wear-resistant composite materials have become a new research field. They are characterized by high strength, good plasticity, good heat resistance, high impact toughness and excellent damping performance. At the same time, they have the high hardness and high wear resistance of ceramic materials, which can overcome the previous problem of wear resistance and toughness restricting each other. In the automotive industry, magnesium die castings have great technical advantages over aluminum in processing, recycling and casting, and magnesium can replace special plastics in automobiles. Therefore, ceramic particle reinforced magnesium alloy composite materials have potential in the automotive industry, broad application prospects and a broad market.
[0006] CN116732402A discloses a nano-particle refined magnesium-yttrium master alloy and a preparation method thereof. The nano-particle refined magnesium-yttrium master alloy of the present invention comprises the following raw materials by weight percentage or volume percentage: yttrium 30-35 wt.%, nano-TiCN particles 1.5-2.5 vol.%, and the balance magnesium, wherein the raw materials magnesium and yttrium are both from commercial Mg-Y master alloy. The commercial Mg-Y master alloy is completely melted in a high-temperature resistance furnace, and fully preheated TiCN nanoparticles coated with aluminum foil are added, and dispersed by ultrasonic technology, stirred evenly and kept warm before casting and forming; the rare earth magnesium alloy is prepared using the raw material, and the rare earth phase refinement effect is more obvious, and the magnesium phase is also significantly refined.
[0007] CN1312303C discloses a magnesium-based spherical quasi-crystal master alloy and a manufacturing method thereof, belonging to the field of metal materials and their preparation. The invention is characterized in that a magnesium-based icosahedral quasi-nanoscale Mg x Zn u Y w Mn t Ca s spherical quasi-crystal master alloy is obtained under high pressure solidification conditions after microalloying and electric pulse inoculation treatment, and the chemical composition (in terms of mass fraction wt%) is: Mg 40.00-45.00%, Zn 45.50-55.00%, Mn 0.50-4.50%, Y 1.00-4.50%, Ca 0.10-1.00%. Its cast structure is characterized by a multiphase structure of uniform icosahedral quasi-nanoscale Mg x Zn u Y w Mn t Ca s spherical quasi-crystal phase + α-Mg + quasi-crystal phase and α-Mg eutectic structure + MgZn crystalline phase, wherein the volume relative content of the spherical quasi-crystal phase of Mg x Zn u Y w Mn t Ca s accounts for 30-40% of the total volume of the master alloy. This master alloy can be produced on a large scale, can be used as a reinforcing phase to strengthen magnesium-based alloys and their composite materials, and can improve the strength, toughness, heat resistance and creep resistance of magnesium alloys. Summary of the invention
[0008] The purpose of the present invention is to provide a ceramic reinforced magnesium alloy with high hardness, high tensile strength and good elongation based on composite magnetic field treatment and a die-casting process thereof.
[0009] The technical solution of the present invention is as follows: A ceramic reinforced magnesium alloy based on composite magnetic field treatment is characterized in that: a standard grade magnesium-based alloy is used as a matrix, rare earth magnesium intermediate alloy and nano-scale ceramic particles are added in a molten state, and the alloy is obtained by composite electromagnetic stirring of the melt mainly with a rotating magnetic field and supplemented by a pulsed magnetic field.
[0010] The rare earth magnesium master alloy is an alloy of rare earth lanthanum or rare earth cerium, the effective mass percentage of rare earth is 25% to 30%, and the particle size is 5 to 8 mm; The addition amount of the rare earth magnesium master alloy is 0.5at%~0.75at%; The amount of the nano-scale ceramic particles added is 0.5 at % to 3 at %; The nano-scale ceramic particles are SiO2 or SiC ceramic particles; A die-casting process for ceramic-reinforced magnesium alloy based on composite magnetic field treatment, characterized in that it comprises the following steps: (1) Use resistance melting furnace and crucible to melt standard grade die-casting magnesium alloy; (2) Add nano-ceramic particles, cut magnesium alloy, and rare earth magnesium master alloy into the crucible in sequence; (3) After melting, keep the mixture warm and place the crucible (mixed magnesium liquid) on the electromagnetic treatment platform; (4) starting a pulse magnetic field and a rotating magnetic field to perform electromagnetic treatment on the magnesium liquid in the crucible; (5) Operate the die-casting machine to complete the die-casting.
[0011] The nano-ceramic particles, the cut magnesium alloy and the rare earth magnesium master alloy are sequentially added into the crucible in step (2), and the preheated magnesium alloy is placed on the rare earth magnesium master alloy, and the preheating temperature is 350°C; The heat preservation and standing time in step (3) is more than 30 minutes; In step (4), a pulse electromagnetic field is applied first, with parameters: frequency 0-80 Hz, current 0-150 A, duty cycle 10%-80%, and action time 30 s-60 s; then a rotating electromagnetic field is applied, with parameters: frequency 0-80 Hz, current 0-100 A, and action time 30 s-60 s; In step (5), the die casting machine is operated by first starting the die casting machine and setting the parameters: slow speed 0.5-0.8 m / s, fast speed 4-5 m / s, fast position 250-260, boost position 255-265, injection time 3.2-3.5 s, cooling time 3-3.5 s, oil temperature circulation machine working temperature: 180-220°C, and setting the die casting machine to manual mode; performing 10-15 die castings in advance, and waiting for the temperature of the die casting machine mold, barrel and punch to reach 180-220°C, using a graphite stirring rod to manually stir the melt in the crucible 2-3 times during the insulation period; after the die casting machine is in place, manual pouring is used, and the molten metal enters the die casting machine barrel, and the pouring insulation temperature is 680-700°C. After the pouring is completed, the die casting machine is delayed for 0.8s-1.2s to inject the mold.
[0012] The beneficial effects of the present invention are: after adding light rare earth La / Ce to magnesium alloy, a needle-shaped Al11La3 phase of strengthening phase is precipitated and the amount of β-Mg17Al12 phase is reduced, which can improve the hardness, tensile strength and elongation of the alloy; On the one hand, the volume force (Lorentz force) generated by the application of an electromagnetic field can produce forced convection, and the uniformity of alloy components of different densities can be improved by specific control of the convective transport process of the melt (semi-solid melt), thereby improving segregation; on the other hand, the electromagnetic effect can promote nucleation and optimize the microstructure by affecting the melt microstructure. Another advantage of the pulsed magnetic field is that it improves the fluidity of the melt during the die-casting filling process, which can significantly reduce the occurrence of casting defects caused by flow. Combining the advantages of rotating and pulsed magnetic fields, the composite electromagnetic stirring technology of rare earth magnesium alloys is realized. The rotating magnetic field is the main one, and the pulsed magnetic field is the auxiliary one to produce the melt stirring effect, which drives the ceramic particles, rare earth phases and other components to produce relative movement. After a certain period of action, the technical effect of relative dispersion and homogenization is achieved, which can improve the tensile strength and elongation of the alloy. Take the mainstream magnesium alloy AZ91 as an example: Comparative test tensile strength test data table BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is the metallographic diagram of AZ91D-xLa with different La contents; in the figure: (a) x=0, (b) x=0.5, (c) x=0.75, (d) x=1, (e) x=3, (f) x=5; Figure 2 These are SEM and surface scan images; in the figure: (a) is AZ91D; (b) is AZ91D-0.75La; Figure 3 The metallographic structure diagram of AZ91D magnesium alloy with 1.5% ceramic particles added by mass; Figure 4 This is the metallographic structure diagram of AZ91D magnesium alloy with 1% ceramic particles added by mass; Figure 5 It is the metallographic structure diagram of AZ91D magnesium alloy with 0.5% ceramic particles added by mass; Figure 6 This is a scanning electron microscope image of an alloy with 1% by mass ceramic particles (SiO2); Figure 7 This is the scanning electron microscope EDS layered image of 1% ceramic particles (SiO2) by mass; Figure 8 This is a scanning electron microscope image of the Si element surface of a ceramic particle (SiO2) with a mass percentage of 1%; Fig. 9 This is the point scan energy spectrum analysis diagram of 1% ceramic particles (SiO2); Fig.10This is the scanning electron microscope EDS layered image of ceramic particles (SiO2) with a mass percentage of 1.5%. In the figure: the upper figure is the electron image (SE), and the lower figure is the EDS layered image; Fig.11 This is a scanning electron microscope image of the Si element surface of ceramic particles (SiO2) with a mass percentage of 1.5%; Fig.12 This is a point scan energy spectrum analysis diagram of ceramic particles (SiO2) with a mass percentage of 1.5%. DETAILED DESCRIPTION
[0014] The present invention is further described below in conjunction with the embodiments, but does not constitute a limitation on the scope of protection of the present invention: Example 1
[0015] (1) A quantitative melting furnace is used to melt the magnesium alloy grade (AZ91D) for die casting; (2) Add Mg-La master alloy (La mass percentage 30%, particle size 8 mm) to the bottom of the furnace, place a magnesium ingot (preheated to 350°C) on top of the master alloy, stir with a stainless steel stirring rod after the magnesium alloy is completely melted, and let it stand for 30 minutes. (3) Start the die-casting machine (set parameters: slow speed 0.5~m / s, fast speed 4.5m / s, fast position 260, boost position 265, injection time 3.5s, cooling time 3.5s), oil temperature circulation machine (working temperature: 180℃), and set the die-casting machine to semi-automatic mode; (4) Perform 12 die castings in advance, and wait until the temperature of the die, barrel and punch of the die casting machine reaches 180°C. Start the pulse magnetic field generating device to apply a pulse magnetic field to the molten metal in the transmission tube; start the rotating magnetic field generating device to apply a rotating magnetic field to the molten metal in the transmission tube.
[0016] (5) Add 3% by weight (calculated based on the total weight of the magnesium alloy and master alloy added to the furnace) of nano-scale ceramic particles (SiO2, SiC, etc.) to the crucible feeding port and stir manually twice; (6) After the die-casting machine is in place, the negative pressure pump of the pouring system is automatically started to pump the magnesium-based ceramic mixed melt into the transmission pipe. The mixed melt first enters the rotating electromagnetic field action area (parameters: frequency 20Hz, current 35A), and then enters the pulsed electromagnetic field action area (parameters: frequency 20Hz, current 100A, duty cycle 40%); (7) The pouring system casting pump pushes 500g (total mass of product, runner and handle) of ceramic mixed melt into the barrel of the die-casting machine; (8) After pouring is completed, the die-casting machine's injection rod automatically pushes the ceramic mixed molten metal into the mold cavity, and the subsequent die-casting actions are automatically completed according to the above step (3), and the product manufacturing is completed. Example 2
[0017] (1) Using a quantitative melting furnace to melt the magnesium alloy grade (AZ61) for die casting; (2) Add Mg-Ce master alloy (Ce mass percentage 30%, particle size 7 mm) to the bottom of the furnace, place a magnesium ingot (preheated to 350°C) on top of the master alloy, stir with a stainless steel stirring rod after the magnesium alloy is completely melted, and keep it warm for 30 minutes before letting it stand. (3) Start the die-casting machine (setting parameters: slow speed 0.8m / s, fast speed 5m / s, fast position 250, boost position 255, injection time 3.2s, cooling time 3s), oil temperature circulation machine (working temperature: 170℃), and set the die-casting machine to semi-automatic mode; (4) Perform 15 die castings in advance, and wait until the temperature of the die, barrel and punch of the die casting machine reaches 170°C. Start the pulse magnetic field generating device to apply a pulse magnetic field to the molten metal in the transmission tube; start the rotating magnetic field generating device to apply a rotating magnetic field to the molten metal in the transmission tube.
[0018] (5) Add 5% by weight (calculated based on the total weight of the magnesium alloy and the master alloy added to the furnace) of nano-scale ceramic particles (SiO2) to the crucible feeding port and stir manually for 3 times; (6) After the die-casting machine is in place, the negative pressure pump of the pouring system is automatically started to pump the magnesium-based ceramic mixed melt into the transmission pipe. The mixed melt first enters the rotating electromagnetic field action area (parameters: frequency 20Hz, current 40A), and then enters the pulse electromagnetic field action area (parameters: frequency 25Hz, current 125A, duty cycle 50%). (7) The pouring system casting pump pushes 800g (total mass of product, runner and handle) of ceramic mixed molten liquid into the barrel of the die-casting machine; (8) After pouring is completed, the die-casting machine's injection rod automatically pushes the ceramic mixed molten metal into the mold cavity, and the subsequent die-casting actions are automatically completed according to the above step (3), and the product manufacturing is completed.
[0019] Reference Figure 1 The main reason why the addition of La to AZ91D leads to a decrease in the β-Mg17Al12 phase is that the Al element in β-Mg17Al12 and the rare earth La preferentially generate a new rare earth compound Al2La due to the difference in electronegativity. Therefore, an appropriate amount of La should be added to AZ91D to increase the dispersion of the second phase of the alloy and increase the number of point-like β phases and needle-like rare earth compounds.
[0020] Reference Figure 2 The morphology of each phase and the distribution of elements in the alloy can be determined. The alloy was subjected to SEM electron scanning and energy spectrum analysis (EDS). The results are as follows Figure 2 As shown. Figure 2(a) It can be seen that the continuous network structure in AZ91D is β-Mg17Al12, which corresponds to the metallographic diagram. Figure 2 (b) It can be seen that after adding rare earth La to AZ91D, the continuous network β-Mg17Al12 becomes discontinuous, and some of it is free in the matrix in the form of particles. At the same time, a large number of new needle-shaped compounds are Al2La, and the Al2La in the figure has already shown agglomeration.
[0021] Reference Figure 3 , 4 5 and 6 are metallographic organization diagrams of adding different percentages. The gray-black spotted phase in the middle diagram is the agglomerated ceramic particles. Under the metallographic microscope, the particle size of the ceramic particles is measured according to the ruler and is between several microns and tens of microns.
[0022] Reference Figure 6 , 7 , Figure 6 and Figure 7 For the same field of view of the scanning electron microscope, Figure 7 The Si element is shown in yellow in the SEM EDS layer diagram. Comparing the two diagrams, we can see that some ceramic particles (SiO2) are distributed in the magnesium matrix, while others are distributed around the magnesium-aluminum phase.
[0023] Reference Figure 8 , Figure 8 The middle yellow part (irregular particle phase in the red circle) is 1% SiO2 ceramic particles. It can be seen that the ceramic particles are relatively evenly dispersed in the rare earth magnesium alloy matrix, and the particles are agglomerated in irregular shapes, ranging from tens of microns to a few microns.
[0024] Reference Fig. 9 The shapes of several ceramic particles (SiO2) are irregular, ranging from a few microns to more than ten microns. According to the point scanning energy spectrum analysis data, the mass ratio of Si to O elements can be calculated to determine that they are SiO2.
[0025] Reference Fig.10 , Fig.10 The two pictures in the middle are the same field of view of the scanning electron microscope. Fig.10 The Si element is shown in yellow in the SEM EDS layer diagram. Comparing the two diagrams, we can see that a small number of ceramic particles (SiO2) are distributed in the magnesium matrix, while most are distributed around the magnesium-aluminum phase.
[0026] Reference Fig.11 The yellow part in the figure (irregular particle phase in the red circle) is 1.5% SiO2 ceramic particles. It can be seen that the ceramic particles are relatively evenly dispersed in the rare earth magnesium alloy matrix, and the particles are agglomerated in an irregular shape, ranging from tens of microns to a few microns.
[0027] Reference Fig.12 The morphology of dozens of agglomerated ceramic particles (SiO2) is irregular, ranging from a few microns to more than ten microns. According to the point scanning energy spectrum analysis data in Table 1 and Table 2, the ceramic phase can be determined to be SiO2 by calculating the mass ratio of Si and O elements.
[0028] Table 1 Total spectrum chart of distribution diagram of relevant elements in tissues:
[0029] Table 2 Total spectrum chart of distribution diagram of relevant elements in tissues:
Claims
1. A ceramic-reinforced magnesium alloy based on composite magnetic field treatment, characterized in that: The alloy is obtained by taking standard grade magnesium-based alloy as the matrix, adding rare earth magnesium master alloy and nano-scale ceramic particles in the molten state, and electromagnetically stirring the melt mainly with a rotating magnetic field and supplemented by a pulsed magnetic field.
2. The ceramic-reinforced magnesium alloy based on composite magnetic field treatment according to claim 1 is characterized in that: The rare earth magnesium intermediate alloy is an alloy of rare earth lanthanum or rare earth cerium, the effective mass percentage of rare earth is 25% to 30%, and the particle size is 5 to 8 mm.
3. The ceramic-reinforced magnesium alloy based on composite magnetic field treatment according to claim 1 is characterized in that: The addition amount of the rare earth magnesium master alloy is 0.5 at % to 0.75 at %.
4. The ceramic-reinforced magnesium alloy based on composite magnetic field treatment according to claim 1 is characterized in that: The added amount of the nano-scale ceramic particles is 0.5 at % to 3 at %.
5. The ceramic-reinforced magnesium alloy based on composite magnetic field treatment according to claim 1 is characterized in that: The nano-scale ceramic particles are SiO2 or SiC ceramic particles.
6. A die-casting process for ceramic-reinforced magnesium alloy based on composite magnetic field treatment according to any one of claims 1 to 5, characterized in that: The steps include: (1) Use resistance melting furnace and crucible to melt standard grade die-casting magnesium alloy; (2) Add nano-ceramic particles, cut magnesium alloy, and rare earth magnesium master alloy into the crucible in sequence; (3) After melting, keep the mixture warm and place the crucible on an electromagnetic treatment platform; (4) starting a pulse magnetic field and a rotating magnetic field to perform electromagnetic treatment on the magnesium liquid in the crucible; (5) Operate the die-casting machine to complete the die-casting.
7. The die-casting process of ceramic-reinforced magnesium alloy based on composite magnetic field treatment according to claim 6 is characterized in that: Nano-ceramic particles, cut magnesium alloy and rare earth magnesium master alloy are sequentially added into the crucible in step (2), and a preheated magnesium alloy is placed on top of the rare earth magnesium master alloy, with the preheating temperature being 350°C.
8. The die-casting process of ceramic-reinforced magnesium alloy based on composite magnetic field treatment according to claim 6 is characterized in that: The heat preservation and standing time in step (3) is more than 30 minutes.
9. The die-casting process of ceramic-reinforced magnesium alloy based on composite magnetic field treatment according to claim 6, characterized in that: In step (4), a pulse electromagnetic field is applied first, with parameters: frequency 0-80 Hz, current 0-150 A, duty cycle 10%-80%, and action time 30 s-60 s; and then a rotating electromagnetic field is applied, with parameters: frequency 0-80 Hz, current 0-100 A, and action time 30 s-60 s.
10. The die-casting process of ceramic-reinforced magnesium alloy based on composite magnetic field treatment according to claim 6, characterized in that: In step (5), the die casting machine is operated by first starting the die casting machine and setting the parameters: slow speed 0.5-0.8 m / s, fast speed 4-5 m / s, fast position 250-260, boost position 255-265, injection time 3.2-3.5 s, cooling time 3-3.5 s, oil temperature circulation machine working temperature: 180-220°C, and setting the die casting machine to manual mode; performing 10-15 die castings in advance, and waiting for the temperature of the die casting machine mold, barrel and punch to reach 180-220°C, using a graphite stirring rod to manually stir the melt in the crucible 2-3 times during the insulation period; after the die casting machine is in place, manual pouring is used, and the molten metal enters the die casting machine barrel, and the pouring insulation temperature is 680-700°C. After the pouring is completed, the die casting machine is delayed for 0.8s-1.2s to inject the mold.
Citation Information
Patent Citations
Magnesium base spherical quasi crystal intermediate alloy and its manufacturing method
CN1312303C
Silicon carbide and quasi-crystal / similar phase enhanced Mg-based composite and preparation method thereof
CN103421995A
Preparation method of rare-earth magnesium alloy composite
CN110423914A
Preparation method of nano SiC particle reinforced magnesium-based composite material
CN116254435A
Composite magnetic field solidification structure treatment device and process thereof
CN118002765A
Cited By
Integrated die casting forming method and system based on multi-magnetic field coupling
CN120839023A